2017
DOI: 10.12965/jer.1734904.452
|View full text |Cite
|
Sign up to set email alerts
|

Be seeded or not be seeded? A study with Olympic judo athletes

Abstract: The main purpose of the present study was to calculate the probability—based on a Bayesian approach—to win a medal in the Olympic Games given the athlete is seeded and to verify if the number one ranked athlete has any advantage compared to other seeded athletes concerning his/her chances to be Olympic champion. For this, data from athletes who took part in the London 2012 and Rio 2016 Olympic Games were considered. For males the probability of seeded athletes to win a medal was 41.1% and 42.9%, while for fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 11 publications
0
16
0
3
Order By: Relevance
“…Our results indicated that the seeded wrestlers in the Rio Olympic Games had a high advantage of being an Olympic Champion. Conversely, the probability of winning a medal for male and female judo athletes (Guilheiro and Franchini, 2017) were lower than the probability of winning a medal for male and female wrestlers. Specifically, Guilheiro and Franchini (2017) have reported that the probability of seeded athletes to win a medal was 41.1% and 42.9% for male judo athletes and 35.7% and 44.6% for female judo athletes at London 2012 and Rio 2016, respectively.…”
Section: Conclusion and Recommendationsmentioning
confidence: 81%
See 3 more Smart Citations
“…Our results indicated that the seeded wrestlers in the Rio Olympic Games had a high advantage of being an Olympic Champion. Conversely, the probability of winning a medal for male and female judo athletes (Guilheiro and Franchini, 2017) were lower than the probability of winning a medal for male and female wrestlers. Specifically, Guilheiro and Franchini (2017) have reported that the probability of seeded athletes to win a medal was 41.1% and 42.9% for male judo athletes and 35.7% and 44.6% for female judo athletes at London 2012 and Rio 2016, respectively.…”
Section: Conclusion and Recommendationsmentioning
confidence: 81%
“…Conversely, the probability of winning a medal for male and female judo athletes (Guilheiro and Franchini, 2017) were lower than the probability of winning a medal for male and female wrestlers. Specifically, Guilheiro and Franchini (2017) have reported that the probability of seeded athletes to win a medal was 41.1% and 42.9% for male judo athletes and 35.7% and 44.6% for female judo athletes at London 2012 and Rio 2016, respectively. Therefore, considering this difference, wrestlers will likely give more importance to the World Wrestling Championship organized 11 months before the Olympic Games to increase their chance to be Olympic champion or get an Olympic medal.…”
Section: Conclusion and Recommendationsmentioning
confidence: 81%
See 2 more Smart Citations
“…Além destas potenciais aplicações, o conhecimento gerado a partir da análise técnica, tática e de estrutura temporal, juntamente com aquele oriundo de investigações sobre a demanda energética da luta, tem permitido a elaboração de processos de avaliação mais especí cos. Neste contexto, vale destacar o processo de avaliação física de atletas do boxe 105 , da esgrima 106 , do judô [107][108] -incluindo atletas paralímpicos 109 , do karatê [110][111][112][113][114] e do taekwondo [115][116] , com utilização de testes especí cos -inclusive com a elaboração de tabelas classi catórias [117][118] e análise discriminante entre diferentes testes 119 e/ou em situações especí cas das diferentes modalidades [120][121][122] . A compreensão de como treinam os atletas que participaram dos Jogos Olímpicos 123 , de quais competições participam durante o processo de quali cação para esta, com determinação da importância relativa quanto ao posicionamento em "rankings" internacionais [124][125][126] e do intervalo ideal entre estas competições para a maximização do desempenho 127 , permite melhor planejamento do processo de treinamento, além da elaboração de estudos com maior validade ecológica.…”
Section: Treinamento Em Modalidades Esportivas De Combateunclassified